Níveis de metais pesados (Cd, Cr, Cu, Fe) em solos de manguezais de São Caetano de Odivelas – Pa - Alves, Railene de Fátima T. (Museu Paraense Emílio Goeldi, 2023)
Mangroves are ecosystems that have a particular vegetation, their soil is muddy and saline, has a high content of organic matter caused by the high biological productivity of the environment and by detritus from mangrove plants and algae. It is one of the most important environments for maintaining the natural resources of the coastal zone. Despite its great importance, these environments are susceptible to degradation due to anthropic actions. The growing urban, touristic and industrial development of the cities, without an adequate sanitation planning, favors the release of urban and industrial effluents in the rivers, with serious pollution threats to this ecosystem. The contamination of these environments by heavy metals, originating from these residues, can occur through atmospheric deposition, through fluvial transport, and through tides. The accumulation of these metals in mangrove sediments is associated with the physical-chemical conditions of the interstitial water and sediments. The present work aimed to verify the levels of heavy metals (Cd, Cr, I and Fe) in mangrove soils as a way to contribute to the generation of information about the functioning of these ecosystems. The study was conducted in the municipality of São Caetano de Odivelas, northeast coast of the State of Pará, where 3 soil profiles were selected (P2, P4 and P5), collected at a depth of approximately 3m, with the help of a 1m mud auger, coupled with two 1m extensions each. The procedures for preparation and laboratory analysis were done according to the methodology described in EMBRAPA (1997). Preliminary results showed an increase in soil acidity when submitted to natural drying (Fine Air Dried Soil - TFSA), varying in pH range (in H20) from 2.85 to 5.77. Under field conditions (wet sample), the acidity remained lower, with pH indices (in water) ranging from 4.86 to 7.22. The remaining analytical data are in progress.